2017
DOI: 10.1088/1742-6596/896/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of process parameters on adhesive wear under hot stamping conditions

Abstract: Abstract. Current challenges like increasing safety standards and reducing fuel consumption motivate lightweight construction in modern car bodies. Besides using lightweight workpiece materials like aluminum, hot stamping has been established as a key technology for producing safety relevant components. Producing hot stamped parts out of ultra-high strength steels offers the possibility to improve the crash performance. At the same time the weight of car structure is reduced by using thinner sheet thicknesses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, the transfer layer continued to grow at the leading edge at a rapid rate, thus resulting in early failure due to severe galling (about 250 mm total sliding). This has also been discussed by Schwingenschlögl et al [22]; more adhesion occurred at a higher load in conjunction with the enhanced sintering effect at higher temperatures. It is important to note that the coefficient of friction reported in this figure corresponds to the most stable part of the friction curves and the curve for 15 MPa contact pressure was relatively stable only for about 2 mm of sliding distance.…”
Section: Frictional Behavioursupporting
confidence: 72%
“…However, the transfer layer continued to grow at the leading edge at a rapid rate, thus resulting in early failure due to severe galling (about 250 mm total sliding). This has also been discussed by Schwingenschlögl et al [22]; more adhesion occurred at a higher load in conjunction with the enhanced sintering effect at higher temperatures. It is important to note that the coefficient of friction reported in this figure corresponds to the most stable part of the friction curves and the curve for 15 MPa contact pressure was relatively stable only for about 2 mm of sliding distance.…”
Section: Frictional Behavioursupporting
confidence: 72%
“…In consequence, the automotive sector, which is the industrial application where hot stamping is most implanted, uses extensively hot work tool steels. Hot stamping die related friction and wear have been studied extensively employing hot work tool steels, with 1.2343 [12][13][14][15][16], 1.2344 [17][18][19][20][21][22][23], and 1.2367 [18,24] as the most frequent choices. Some have been also employed for aluminum coated steel hot stamping [20], together with proprietary steels such as Toolox ® 44 from SSAB [21], QRO90 ® Supreme from Uddeholm [2,25], or W300 ® from Böhler [4].…”
mentioning
confidence: 99%
“…• reciprocating pin-on-disk [2,3,26,27], • reciprocating ball-on-disk [20], • regular ball-on-disk [13][14][15]18,21,27], • block-on-ring [17], • hot strip drawing [4,16,[22][23][24][25], • cross cylinder [19], • block-on-cylinder [13], • and top hat drawing test [27].…”
mentioning
confidence: 99%
“…Merklein et al (Merklein, Wieland and Fell 2014) and Schwingenschlögl et al (Schwingenschlögl, Weldi and Merklein 2017) observed the opposite: a decrease in wear height for increasing contact pressure. This effect is contradictory to Archard's formula and expectations.…”
Section: Velocitymentioning
confidence: 96%
“…Wieland et al (Wieland and Merklein 2015) observed a marginal influence of the blank temperature. Schwingenschlögl et al (Schwingenschlögl, Weldi and Merklein 2017) observed an increased material transfer at higher temperatures and relate this to an increased diffusion rate.…”
Section: Forming Temperaturementioning
confidence: 97%